From Synapse to Supper: A Food Preference Recipe with Olfactory Synaptic Ingredients - Nakahara, Thiago S.; Carvalho, Vinicius M.A.; Papes, Fabio (Neuron (Cambridge, Mass.), 2020)
C1ql3 protein and its receptor Bai3 are involved in synaptic organization and function. In this issue of Neuron, Wang et al. (2020) report that both are essential for synaptic function between the anterior olfactory nucleus and the olfactory bulb and for the generation, but not recall, of associative olfactory memories determining food preference in mice. C1ql3 protein and its receptor Bai3 are involved in synaptic organization and function. In this issue of Neuron, Wang et al. (2020) report that both are essential for synaptic function between the anterior olfactory nucleus and the olfactory bulb and for the generation, but not recall, of associative olfactory memories determining food preference in mice.